2003
DOI: 10.4049/jimmunol.170.12.5965
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Effect of HIV-1 Plasma Viremia on B Cell Costimulatory Function

Abstract: HIV infection leads to numerous immunologic defects, including impaired B cell function. An effective humoral response requires bidirectional interactions between B cells and CD4+ T cells, critical of which are interactions between CD80/CD86 expressed on activated B cells and CD28 expressed on responder CD4+ T cells. In the present study, we examined the effect of active HIV replication on B cell costimulatory function. Induction of CD80/CD86 on B cells following B cell receptor and CD40 triggering and respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
86
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 43 publications
4
86
0
3
Order By: Relevance
“…6,31 In the group of treatment-naive patients we observed that the percentage of circulating memory B lymphocytes is inversely correlated with HIV viremia, indicating that virus-induced immune activation may directly contribute to the loss of memory B cells and to B-cell dysfunctions, as recently suggested. 24 On the other hand and perhaps simultaneously, high antigenic pressure might be a bystander driving force to activate B cells to produce polyclonal Abs. 25 The B-cell hyperactivity found in our and previous studies can be considered as a paradox since a poor B-cell response occurs in patients after immunization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,31 In the group of treatment-naive patients we observed that the percentage of circulating memory B lymphocytes is inversely correlated with HIV viremia, indicating that virus-induced immune activation may directly contribute to the loss of memory B cells and to B-cell dysfunctions, as recently suggested. 24 On the other hand and perhaps simultaneously, high antigenic pressure might be a bystander driving force to activate B cells to produce polyclonal Abs. 25 The B-cell hyperactivity found in our and previous studies can be considered as a paradox since a poor B-cell response occurs in patients after immunization.…”
Section: Discussionmentioning
confidence: 99%
“…17,22 In addition, HIV-1 itself may directly affect B-cell activation and dysfunction, inducing the appearance of a subset of CD21 Ϫ B cells which have been proposed to contribute to increased antibody production. 23,24 A recent work by Hunziker et al 25 has suggested that naive B cells represent an important source of hypergammaglobulinemia and autoantibody production in chronic viral infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that after reduction of HIV plasma viremia by antiretroviral therapy, B cell abnormalities subside, especially those thought to be directly or indirectly associated with virus-induced aberrant immune activation (4)(5)(6). We have demonstrated previously both in longitudinal and cross-sectional analyses that overrepresentation of a distinct B cell population, defined by reduced expression of CD21 and increased secretion of immunoglobulins (7), is likely to be responsible for several of the B cell defects that have been associated with ongoing HIV replication (8)(9)(10). Among the B cell alterations that correlate with HIV plasma viremia and decreased survival of B cells is an increased expression of CD95 accompanied by an increased susceptibility to CD95 ligand (CD95L)-mediated cell death (8).…”
mentioning
confidence: 97%
“…A role for humoral immunity in this process is supported by the common development of hypergammaglobulinemia in chronically infected individuals, associated with B cell hyperactivation, clonal expansions and deletions, and deficient costimulatory function. [1][2][3][4][5][6] It is unclear, however, if these abnormalities are the result of viremia and a direct effect of virus on B lymphocytes or, alternatively, mediated by long-term infectioninduced changes in T-cell subsets and cytokine production. To assess the early effect of HIV infection on the integrity of the peripheral B cell repertoires, we analyzed the B cellreceptor diversity in a longitudinal cohort of 10 affected individuals who had been treated with HAART immediately after diagnosis and 10 infected individuals who chose not to be treated.…”
mentioning
confidence: 99%